Identifikasi Penyakit Pada Kambing Menggunakan Metode Fuzzy K-Nearest Neighbor (F-KNN) - Basuki Rahmat Rialdi; Nurul Hidayat; Suprapto Suprapto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Goat (Capra Aegragus Hircus) is one of the animals raised by humans. However, goat cattle business will experience constraints when the goats are infected with the disease. In addition to causing harm, the disease can also reduce public interest to goat breeding. So the system was made to identify the disease in goat farms, so the breeder could know the type of disease that attacked and handled it appropriately. The method used is k-nearest neighbor and fuzzy. The first step of this method includes trainer data that contains symptoms of the disease. Then the classification uses k-nearest neighbor. After the implementation and testing, obtained the highest accuracy of 96% at K which is worth 9. From these results can be concluded that the results of the system and experts are aligned and have positive accuracy